1998
DOI: 10.1523/jneurosci.18-04-01196.1998
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein and Tyrosine Kinases in the Activation of Astrocyte Volume-Activated Chloride Current

Abstract: Astrocytes swell during neuronal activity as they accumulate K+ to buffer the increase in external K+ released from neurons. This swelling activates volume-sensitive Cl- channels, which are thought to be important in regulatory volume decrease and in the response of the CNS to trauma and excitotoxicity. Mitogen-activated protein (MAP) kinases also are activated by cell volume changes, but their roles in volume regulation are unknown. We have investigated the role of tyrosine and MAP kinases in the activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
126
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 48 publications
13
126
4
Order By: Relevance
“…The use of a selective inhibitor of ERK1/2 activity showed that ERK1/2 phosphorylation takes part in the decrease in chloride flux observed after FGF9 exposure. The relationship between mitogen-activated protein kinase pathway and chloride current modulation has already demonstrated in astrocytes and cardiac myocytes [28,29].…”
Section: Discussionmentioning
confidence: 90%
“…The use of a selective inhibitor of ERK1/2 activity showed that ERK1/2 phosphorylation takes part in the decrease in chloride flux observed after FGF9 exposure. The relationship between mitogen-activated protein kinase pathway and chloride current modulation has already demonstrated in astrocytes and cardiac myocytes [28,29].…”
Section: Discussionmentioning
confidence: 90%
“…Intracellular Signaling Mechanisms Involved in the H 2 O 2 Effect on EAA Release-H 2 O 2 activates non-receptor tyrosine kinases of the src family, receptor tyrosine kinases, and, downstream, enzymes of the MAPK cascade (22,39), all of which have been found to contribute to VRAC activation (23)(24)(25). Therefore, we tested for the contribution of tyrosine and MAP kinases in mediating the H 2 O 2 effect on swelling-induced EAA release.…”
Section: Hydrogen Peroxide Potentiatesmentioning
confidence: 99%
“…In line with such a suggestion, reactive oxygen species positively modulate the activity of a number of protein kinases, such as tyrosine kinases, mitogen-activated protein kinases (MAPKs), protein kinase C (PKC), and Ca 2ϩ /calmodulin-dependent protein kinase II (CaMKII) (20 -22). All of these kinases have been found to contribute to VRAC activation and/or modulation in a variety of cell types (9,(23)(24)(25)(26)(27)(28). Robust changes in tyrosine phosphorylation and MAPK activity, as well as the translocation of PKC and CaMKII from the cytosol to the membrane fraction, have been found in ischemia (29 -32).…”
mentioning
confidence: 99%
“…Several studies have shown that PD98059-but not SB203580-reversibly blocks hypotonic solution activation of the swelling-sensitive Cl − current in astrocytes (Crepel et al, 1998), cardiac muscle (Du and Sorota, 2000) and cervical cancer cells (Shen et al, 2001). PD98059 also blocks swelling-sensitive K + efflux without affecting the KCC co-transporter (Shen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%